Map-based cloning and characterization of BPH29, a B3 domain-containing recessive gene conferring brown planthopper resistance in rice. (1st July 2015) - Wang, Ying; Cao, Liming; Zhang, Yuexiong; Cao, Changxiang; Liu, Fang; Huang, Fengkuan; Qiu, Yongfu; Li, Rongbai; Luo, Xiaojin
Abstract : A brown planthopper resistance recessive gene, BPH29, was cloned which contained a B3 DNA-binding domain and conferred resistance by a mechanism that was similar to plant defence against pathogens. Abstract: Rice ( Oryza sativa L.) production, essential for global food security, is threatened by the brown planthopper (BPH). The breeding of host-resistant crops is an economical and environmentally friendly strategy for pest control, but few resistance gene resources have thus far been cloned. An indica rice introgression line RBPH54, derived from wild rice Oryza rufipogon, has been identified with sustainable resistance to BPH, which is governed by recessive alleles at two loci. In this study, a map-based cloning approach was used to fine-map one resistance gene locus to a 24kb region on the short arm of chromosome 6. Through genetic analysis and transgenic experiments, BPH29, a resistance gene containing a B3 DNA-binding domain, was cloned. The tissue specificity of BPH29 is restricted to vascular tissue, the location of BPH attack. In response to BPH infestation, RBPH54 activates the salicylic acid signalling pathway and suppresses the jasmonic acid/ethylene-dependent pathway, similar to plant defence responses to biotrophic pathogens. The cloning and characterization of BPH29 provides insights into molecular mechanisms of plant–insect interactions and should facilitate the breeding of rice host-resistant varieties.